(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
Valparaíso is a paradigmatic example of Capitalism’s crisis and instabilities and of Latin American modernization during the XIX and XX centuries. Its history of wealth, segregation, cosmopolitism, and decadence is projected in the writings about the city, which we problematize based on the concepts of deterritorialization and alienation, since we perceive a significant presence of foreign and outsider authors in the literary production of Valparaíso. To analyze the textual elaboration of some subjectivities whose points of reference and cultural frameworks are tensioned in Valparaíso, we propose seven periods: 1) the enlightenment travellers; 2) the foundational debates; 3) modernism and social poetry; 4) the expressionist and imaginist vanguards; 5) the social novel; 6) the provincial novel; 7) and the poetry of exile, where the process reverses and some local poets write about Valparaíso while overseas